LANGUAGE DEVELOPMENT IN PRESCHOOL (5-7 YEARS) CHILDREN WITH DYSLEXIA: A PSYCHOLINGUISTIC STUDY - Siregar, Fadlan Hanafi; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
The main function of language is to communicate and interact with others. The process of language acquisition begins in childhood to adulthood. Dyslexia is one type of language disorder that can be an obstacle to children's language development. Dyslexia affects the neurological function of the brain that functions to process language. Dyslexia also affects children's writing ability. The purpose of this study is to describe and explain what dyslexia is, what are the symptoms, causes, and dyslexia treatment efforts. This study uses a literature review research type. The results of the study showed that children with dyslexia often face difficulties in recognizing letters, spelling words, and understanding texts. Environmental factors, such as family support and learning methods, also affect children's language development. This study is expected to provide insight to teachers and parents about the importance of the right approach in helping children with dyslexia learn language better.